2018
DOI: 10.1159/000484415
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Measure of the International Classification of Diseases-11 Adjustment Disorder: Investigation of Psychometric Properties in an Adult Help-Seeking Sample

Abstract: Adjustment disorder is one of the most prevalent mental disorders. However, there are almost no measures available for its assessment. We aimed to analyze the psychometric properties of a brief version of the International Classification of Diseases (ICD)-11 adjustment disorder scale (Adjustment Disorder New Module-8; ADNM-8) in a help-seeking sample. Data from 1,174 participants with an average age of 35 years who registered for the internet-based self-help adjustment disorder intervention were analyzed. Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 16 publications
(34 reference statements)
6
77
0
3
Order By: Relevance
“…Previous studies supported the factor structure of the brief 8-item ADNM-8 measure (Kazlauskas, Zelviene, Lorenz, et al, 2017), and good psychometric characteristics of the ADNM-8 were reported in several studies (Ben-Ezra et al, 2018;Kazlauskas et al, 2018;Lorenz et al, 2018a;Zelviene et al, 2017). In this study, Cronbach's α was .89 for the total ADNM-8 scale, α = .87 was for the ADNM-8 preoccupation subscale, and α = .79 for the ADNM-8 failure to adapt subscale.…”
Section: Adjustment Disorder Symptomssupporting
confidence: 79%
See 2 more Smart Citations
“…Previous studies supported the factor structure of the brief 8-item ADNM-8 measure (Kazlauskas, Zelviene, Lorenz, et al, 2017), and good psychometric characteristics of the ADNM-8 were reported in several studies (Ben-Ezra et al, 2018;Kazlauskas et al, 2018;Lorenz et al, 2018a;Zelviene et al, 2017). In this study, Cronbach's α was .89 for the total ADNM-8 scale, α = .87 was for the ADNM-8 preoccupation subscale, and α = .79 for the ADNM-8 failure to adapt subscale.…”
Section: Adjustment Disorder Symptomssupporting
confidence: 79%
“…The symptom intensity and diagnostic status of ICD-11 adjustment disorder were assessed using the brief Adjustment Disorder New Module-8 (ADNM-8) scale (Kazlauskas et al, 2018), which is a revised version of the ADNM-20 scale (Einsle, Köllner, Dannemann, & Maercker, 2010). The ADNM measure is widely used in ICD-11 adjustment disorder research (Kazlauskas, Zelviene, Lorenz, et al, 2017;…”
Section: Adjustment Disorder Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADNM-20 showed satisfactory properties regarding factor structure, internal consistency, retest-reliability, and construct validity (Bley, Einsle, Maercker, Weidner, & Joraschky, 2008; Einsle et al, 2010; Glaesmer et al, 2015) in previous studies. The use of the ADNM-8 found initial support in two previous studies (Kazlauskas, Gegieckaite, Maercker, Eimontas, & Zelviene, 2018; Zelviene et al, 2017). The internal consistency in this study was α = .87.…”
Section: Methodsmentioning
confidence: 75%
“…However, it also includes four associated symptom clusters of avoidance (four items), depression (three items), anxiety (two items) and impulsivity (three items). There have been further abbreviations of the ADNM, namely an 8‐item version (ADNM‐8) and an ‘ultra‐brief’ 4‐item version (ADNM‐4) both intended to focus specifically on the core AjD symptoms of preoccupations and failure to adapt.…”
Section: Aims Of the Studymentioning
confidence: 99%